2020
DOI: 10.1002/rcm.8668
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of glyphosate and aminomethylphosphonic acid from microbiome reactor fluids

Abstract: Rationale Glyphosate is one of the most widely used herbicides and it is suspected to affect the intestinal microbiota through inhibition of aromatic amino acid synthesis via the shikimate pathway. In vitro microbiome bioreactors are increasingly used as model systems to investigate effects on intestinal microbiota and consequently methods for the quantitation of glyphosate and its degradation product aminomethylphosphonic acid (AMPA) in microbiome model systems are required. Methods An optimized protocol enab… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…Although it is not possible to define bacterial species as either ‘good’ or ‘bad’, Proteobacteria are generally regarded to have a negative influence on human health ( Shin et al, 2015 ). In a recent study using bioreactor systems inoculated with colonic bacteria from German Landrace pigs, glyphosate concentrations remained unchanged after a short two day exposure ( Fritz-Wallace et al, 2020 ). However, it remains unclear as to whether glyphosate metabolic pathways exist in the human gut microbiome.…”
Section: Discussionmentioning
confidence: 99%
“…Although it is not possible to define bacterial species as either ‘good’ or ‘bad’, Proteobacteria are generally regarded to have a negative influence on human health ( Shin et al, 2015 ). In a recent study using bioreactor systems inoculated with colonic bacteria from German Landrace pigs, glyphosate concentrations remained unchanged after a short two day exposure ( Fritz-Wallace et al, 2020 ). However, it remains unclear as to whether glyphosate metabolic pathways exist in the human gut microbiome.…”
Section: Discussionmentioning
confidence: 99%
“…Since glyphosate is an organophosphate compound, this observation may originate from previously unknown biotransformation of glyphosate. In another bioreactor study investigating the porcine gut microbiota, it was found that AMPA was produced by the bacterial communities from the degradation of glyphosate (Fritz-Wallace et al, 2020). A more recent study of the metabolism of glyphosate in vitro by the use of human fecal suspension (HFS) samples found that biotransformation of glyphosate seems to be negligible in human gut microbiota from 15 healthy adult humans (Huch et al, 2021) Perhaps the most surprising metabolome changes we observed was the increase in levels of n3 and n6 long chain polyunsaturated fatty acids (PUFA) Some limited groups of bacteria can synthetize distinct unsaturated fatty acids such as arachidonic acid (20:4 n-6), eicosapentaenoic acid (20:5 n-3), and docosahexaenoic acid (22:6 n-3) (Okuyama et al 2007;Yoshida et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Since glyphosate is an organophosphate compound, this observation may originate from previously unknown biotransformation of glyphosate. In another bioreactor study investigating the porcine gut microbiota, it was found that AMPA was produced by the bacterial communities from the degradation of glyphosate (Fritz-Wallace et al, 2020). A more recent study of the metabolism of glyphosate in vitro by the use of human fecal suspension samples found that biotransformation of glyphosate seems to be negligible in human gut microbiota from 15 healthy adult humans (Huch et al, 2021)…”
Section: Discussionmentioning
confidence: 99%
“…Quantification of 2 in this study was based on the previous methods with minor modifications 75 , 76 . Briefly, samples (1 mL) for 2 measurement were taken after 5-day bacterial culture and was centrifuged (10,000 rpm, 5 min, 4 °C).…”
Section: Methodsmentioning
confidence: 99%